Investigating the performance of a novel Anaerobic Sequencing Batch Reactor (AnSBR) and optimisation of operational parameters to treat synthetic winery wastewater - Laing, Marilet (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc Food Sc)--Stellenbosch University, 2016.